2014
DOI: 10.1021/ac502179m
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Chemical Modification by Citric Acid in a Recombinant Monoclonal Antibody

Abstract: Recombinant therapeutic monoclonal antibodies exhibit a high degree of heterogeneity that can arise from various post-translational modifications. The formulation for a protein product is to maintain a specific pH and to minimize further modifications. Generally Recognized as Safe (GRAS), citric acid is commonly used for formulation to maintain a pH at a range between 3 and 6 and is generally considered chemically inert. However, as we reported herein, citric acid covalently modified a recombinant monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…It is worth noting that the intrinsic charge heterogeneity of the unmodified antibody contributed to the multiple bands observed for both enzymatic and chemical conjugates. As is well documented in the literature, these antibody charge variants are due to various post‐translational modifications, such as deamidation, oxidation, glycosylation, or other reactive metabolites (51‐59).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the intrinsic charge heterogeneity of the unmodified antibody contributed to the multiple bands observed for both enzymatic and chemical conjugates. As is well documented in the literature, these antibody charge variants are due to various post‐translational modifications, such as deamidation, oxidation, glycosylation, or other reactive metabolites (51‐59).…”
Section: Resultsmentioning
confidence: 99%
“…However, formulation additives may also participate in unanticipated reactions to increase acidic charge variants. Chumsae et al () showed that a citric acid derivative reacted with the N‐terminal of an IgG1 molecule which led to increased acidic species. Citric acid is widely used in formulations to maintain buffer pH at 3–6 as it is considered chemically inert.…”
Section: Upstream Process Strategies For Charge Variants Controlmentioning
confidence: 99%
“…There was no significant change in free amines of the amine‐MSs in phosphate or acetate buffers for at least four autoclave cycles (Figure ). However, in citrate buffer, there was a loss of ∼7% of amines each cycle; this is attributable to the formation of citric acid anhydride during autoclaving, which forms in acidic citrate solutions and can acylate amine groups …”
Section: Resultsmentioning
confidence: 99%